Campaign Diary, documentary heritage of the teaching of history - Ortega Alfonso, Beatriz G.; Febles Gómez, Tomás V. (Atenas, 2017)
The study of documentary heritage is a permanent task in the professional pedagogic training of the students in Marxism-Leninism and History major. This article is intended to show the resources of the campaign literature in order to develop the historical culture and to train the critical thinking. It illustrates the example of The Campaign Diary of Jose Eduardo Rosell Malpica, Lieutenant Colonel of the Liberating Army during the 1895’s war, which expose the significant role of primary sources to understand events, personalities and knowledge. The bibliographical revision allowed to reflect and propose procedures that are recommended when working with historical documents.